The Basketball warms-ups - theoretical assumptions and practical solutions - Łubiński, Sebastian; Kosendiak, Jan (Journal of Education, Health and Sport, 2017)
Many authors emphasize the importance of warm-up. Warm-up in team games aims at enhancing the body adaptation to the physical activity and to activate physiological functions from the rest state to the active state. Warm-up brings many different benefits, for example: physiological, psychological, and preventive, regardless of the classification of the above. From a psychological standpoint, the warm-up is performed to create the body "alertness", activity and readiness, and a willingness to act effectively. It was found that the players who perform the correct warm-up are better mentally prepared than those who do not perform it. After a well performed warm-up, the athlete is self-confident and has a positive attitude to the match. It is believed that the warm-up can also be the way to relieve tension and anxiety and to increase concentration and motivation before the match. Warm-up also improves the emotional states and reduces fear of failure. It has been verified that the warm-up, performed under appropriate conditions, improves focus, visual perception, action accuracy, self-confidence, speed and responsiveness, speed of processing and decision making. From the physiological point of view, the warm-up is an activity that adapts the basketball player’s body to an effort. It is an important factor that affects the effect of participation in the competition. Data from the literature suggest that the warm-up individualization is necessary in terms of duration and intensity. There are two types of warm-ups: passive and active. Passive warm-up is the one that is performed by using hot showers, baths, saunas, and steam baths or by using energetics massage. Active warm-up requires a lot of commitment and determination from the athlete during exercises that prepare the body and muscles for an effort. The training measures used during this part of warm-up are the general exercises that improve strength, stretch, coordination, and technical-tactical activities, and activities with the ball or without it. The cognitive purpose of the paper: was to find and develop the best possible pre-match warm-up structures based on current literature. These data were used to determine a "model" (pattern) of optimal warm-up. The practical aim was to formulate guidelines for basketball coaches to develop the warm-up structures, taking into account the duration and proportion of dynamic and static exercises that prepare the body for play. The research material was 12 male players from the basketball team playing in the top tournaments in Poland and in the Tauron Basket League. 11 players were included in the play reliability study, because one of them did not participate in the play and it was impossible to determine his play effectiveness. The team was ranked in the top five of the 2014/2015 league table. The standardized observation method was used in the study. The method consisted in observing people with respect to the purpose of observation, taking into account strictly defined behavioral (reactions) categories the researchers were interested in. To evaluate the players’ effectiveness during the match, the original result sheet of the players’ performance based on the Superlak project was used. As a result of the research, no correlation between the type of warm-up performed by the respondents and the player’s reliability during the match was observed. According to authors, the results allow formulating the following conclusions: • In the Extra-class team, many of the competitors skip the general phase and performed only the specialist phase. There is a division based on the type of exercises (dynamic, static, ball). • Based on the observation made, the warm-up performed by the Extra-class basketball players did not match the warm-up model resulting from the literature recommendations and it did not affect the player’s reliability and performance during the match. • As a practical proposal, trainers should use rational, highly personalized warm-up models.